Răspuns :
(3^5050 + 2 x 3^5050 ) : 3^5051 =
3^5050 ( 1 + 2 x 1 ) : 3^5051 =
3^5050 x 3 : 3^5051 =
3^5051 : 3^5051 =
1
3^5050 ( 1 + 2 x 1 ) : 3^5051 =
3^5050 x 3 : 3^5051 =
3^5051 : 3^5051 =
1
(3^{5050} [/tex] + 2*[tex] 3^{5050} [/tex]):[tex] 3^{5051} [/tex]
dăm factor comun în paranteză pe [tex] 3^{5050} [/tex] şi avem:
[tex] 3^{5050} [/tex] (1+2) : [tex] 3^{5051} [/tex]
[tex] 3^{5050} [/tex] * 3 : [tex] 3^{5051} [/tex]
aplicăm una dintre regulile de calcul cu puteri:
[tex] 3^{5050+1-5051} [/tex]
[tex] 3^{0} [/tex]
1
dăm factor comun în paranteză pe [tex] 3^{5050} [/tex] şi avem:
[tex] 3^{5050} [/tex] (1+2) : [tex] 3^{5051} [/tex]
[tex] 3^{5050} [/tex] * 3 : [tex] 3^{5051} [/tex]
aplicăm una dintre regulile de calcul cu puteri:
[tex] 3^{5050+1-5051} [/tex]
[tex] 3^{0} [/tex]
1